Fabrication and mechanical properties of three-dimensional enhanced lattice truss sandwich structures. (June 2020) - Yang, Wen; Xiong, Jian; Feng, Li-Jia; Pei, Chong; Wu, Lin-Zhi
Topological-reinforcement and material-strengthening were used and employed to improve the mechanical properties of lattice truss sandwich structures. This new type of three-dimensional aluminum alloy lattice truss (named enhanced lattice truss) sandwich structure, with a relative density ranging from 1.7% to 4.7%, was designed and fabricated by interlocking and vacuum-brazing method. The out-of-plane compression and shear properties of the enhanced lattice truss sandwich structures (both as-brazed and age-hardened cores) were experimentally and analytically investigated. Good correlations between analytical predictions and experiment results were achieved. Experimental results showed that the mechanical properties of the enhanced lattice truss cores were sensitive to the unit-cell size and parent-alloy properties (i.e. inelastic buckling and tangential modulus). The compressive and shear characteristics of enhanced lattice truss sandwich structures were discussed and found superior to competing lattice truss structures in low density area (0.046–0.124 g/cm 3 ) of material property charts. The combination of topological-reinforcement and material-strengthening provided a way to achieve lightweight sandwich structures with high specific strengths and low densities.